Efficiency of Transscleral Laser Cytophotocoagulation in Patients with Neovascular Glaucoma - Jamshedovich, Ismoilov Jasur (American Journal of Biomedicine and Pharmacy, 2025)
The effect of transscleral diode laser cyclophotocoagulation on intraocular pressure and visual function in patients with normal-tension glaucoma Transscleral diode laser cyclophotocoagulation (TDLCC) is a well-known effective method for reducing IOP. The modified method of TDLCC has a positive effect on visual function due to coagulation not only of the corona ciliary, but also of the pars plana. Due to this modification of the technique, the biologically active substances of the laser burn penetrate into the vitreous body, and with its flow into the retina and optic nerve head, exerting a vasoactive effect.